Antibacterial cyclopentenones from the coprophilous fungus Clonostachys pseudochroleuca - Annick B. F. Kapche; Paul Eckhardt; Joseph Tchamgoue; Bienvenu Tsakem; Jenifer R. N. Kuete; Aron Trucksess; André-Ledoux Njouonkou; Beaudelaire K. Ponou; Léon A. Tapondjou; Till Opatz; Victor Kuete; Rainer Kalscheuer; et al. (Natural Product Research, 2025)

P14-10 Genome-Wide DNA Methylation Profiles Associated with Diesel Exhaust Particulate Matter in Bladder Spheroids - H.R. Dhaini; W. Abou-Kheir; C. Afif; A. Ghantous; M. Fadel; J. Sciare; D. Courcot; F. Ledoux; A. Kurdi; A. Yehya; N. Fakhri; M. El Kawak (Toxicology Letters, 2025)

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Superheated flash-boiling atomisation effects on spray carbon capture performance using non-aqueous amines - Louis F. Dacanay; Kevin Wan; Julien Manin; Guillaume De Sercey; Peter J. Cragg; Alain Ledoux; Lionel Estel; Cyril Crua (Fuel, 2025)

P21-42 Impact of Organic Extractable Matter (OEM) from PM2.5 collected in Lebanon on human bronchial epithelial cells: insights into autophagy, mitophagy, and cell senescence Activation - M. Chwaikani; A. Verdin; G. Badran; I. Abbas; N. Jaber; M. Roumie; D. Courcot; F. Ledoux; G. Garçon (Toxicology Letters, 2024)

Ascorbate oxidation driven by PM2.5-bound metal(loid)s extracted in an acidic simulated lung fluid in relation to their bioaccessibility - A. Expósito; B. Markiv; M. Santibáñez; M. Fadel; F. Ledoux; D. Courcot; I. Fernández-Olmo (Air Quality, Atmosphere & Health, 2024)
The oxidative potential (OP) is defined as the ability of inhaled PM components to catalytically/non-catalytically generate reactive oxygen species (ROS) and deplete lung antioxidants. Although several studies have measured the OP of particulate matter (PM OP) soluble components using different antioxidants under neutral pH conditions, few studies have measured PM OP with acidic lung fluids. This study provides new insights into the use of acidic rather than neutral fluids in OP assays. Thus, the first aim of this study was to clarify the effect of using an acidic lung fluid on ascorbic acid (AA) depletion. This was achieved by measuring the oxidative potential (OP-AA) of individual compounds known to catalyze the AA oxidation (CuSO 4 , CuCl 2 , and 1,4-NQ) in artificial lysosomal fluid (ALF, pH 4.5), a commonly used acidic simulated lung fluid, and in a neutral fluid (phosphate-buffered saline (PBS1x), pH 7.4). Our results from these individual compounds showed a significant decrease of OP-AA in the acidic fluid (ALF) with respect to the neutral fluid (PBS). Then, the second aim of this work was to investigate whether the OP-AA assay could be applied to PM 2.5 samples extracted in acidic conditions. For this purpose, OP-AA and bioaccessible concentrations of metal(loid)s (V, Mn, Fe, Ni, Cu, Zn, As, Mo, Cd, Sb, and Pb) of PM 2.5 samples collected in an urban-industrial area that were extracted in ALF were analyzed. The mean volume-normalized OP (OP-AAv) value was 0.10 ± 0.07 nmol min −1 m −3 , clearly lower than the values found in the literature at neutral pH. OP-AAv values were highly correlated with the ALF-bioaccessible concentration of most of the studied metal(loid)s, mainly with Cu and Fe.

Genetic insights into recolonization processes of Mediterranean octocorals - D. Aurelle; J. Tariel; F. Zuberer; A. Haguenauer; C. Ribout; M. Masmoudi; H. Kara; L. Chaoui; J. Garrabou; J.-B. Ledoux; M. C. Gambi (Marine Biology, 2020)

Occurrence of aflatoxins in rice and in cassava (Manihot esculenta) products (meal, bread) produced in Guyana - Donna M. Morrison; David R. Ledoux; Lambert F. B. Chester; Coretta A. N. Samuels (Mycotoxin Research, 2019)

Colonization pressure as a risk factor of ICU-acquired multidrug resistant bacteria: a prospective observational study - J. Masse; A. Elkalioubie; C. Blazejewski; G. Ledoux; F. Wallet; J. Poissy; S. Preau; S. Nseir (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

Abnormal spontaneous and harmaline-stimulated Purkinje cell activity in the awake genetically dystonic rat - Mark S. LeDoux; Joan F. Lorden (Experimental Brain Research, 2002)

Measurement of the Contrast Agent Intrinsic and Native Harmonic Response with Single Transducer Pulse Waved Ultrasound Systems - Xander A. A. M. Verbeek; Jean M. Willigers; Peter J. Brands; Léon A. F. Ledoux; Arnold P. G. Hoeks (Annals of Biomedical Engineering, 1999)

Regulation of the neutral phosphatase in Chlamydomonas reinhardi: An immunogenetic study of wild-type and mutant strains - R. Loppes; J. Braipson; R. F. Matagne; A. Sassen; L. Ledoux (Biochemical Genetics, 1977)